An exploration of occupational choices in adolescence: a constructivist grounded theory study - Parsonage, J; Naylor Lund, K; Dawes, H; Almoajil, H; Eklund, M (Taylor and Francis, 2020)
Background: Adolescence is a critical period within the life course, for developing adult occupational competencies and health behaviours. Few studies have considered how 16–17 year olds choose activities and behaviours from an occupational perspective.